2018
DOI: 10.1186/s13071-018-3101-4
|View full text |Cite
|
Sign up to set email alerts
|

Implications of insecticide resistance for malaria vector control with long-lasting insecticidal nets: trends in pyrethroid resistance during a WHO-coordinated multi-country prospective study

Abstract: BackgroundIncreasing pyrethroid resistance has been an undesirable correlate of the rapid increase in coverage of insecticide-treated nets (ITNs) since 2000. Whilst monitoring of resistance levels has increased markedly over this period, longitudinal monitoring is still lacking, meaning the temporal and spatial dynamics of phenotypic resistance in the context of increasing ITN coverage are unclear.MethodsAs part of a large WHO-co-ordinated epidemiological study investigating the impact of resistance on malaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Our results show substantial variation in resistance trends between East and West Africa, as well as within these two regions. Interestingly, ITN coverage was identified as a relatively influential predictor in our models, which is consistent with other studies that have found significant, but spatially variable, increases in pyrethroid resistance associated with the introduction of ITNs [24]. However, in several areas of the central and southern parts of East Africa, such as west Tanzania, ITN coverage has been relatively high (>50%) from 2012 to 2017 [22], but predicted pyrethroid resistance in 2017 was relatively low (Fig 2D).…”
Section: Plos Biologysupporting
confidence: 91%
See 1 more Smart Citation
“…Our results show substantial variation in resistance trends between East and West Africa, as well as within these two regions. Interestingly, ITN coverage was identified as a relatively influential predictor in our models, which is consistent with other studies that have found significant, but spatially variable, increases in pyrethroid resistance associated with the introduction of ITNs [24]. However, in several areas of the central and southern parts of East Africa, such as west Tanzania, ITN coverage has been relatively high (>50%) from 2012 to 2017 [22], but predicted pyrethroid resistance in 2017 was relatively low (Fig 2D).…”
Section: Plos Biologysupporting
confidence: 91%
“…Since 2015, deltamethrin has been the only pyrethroid reported to be used in mass IRS campaigns along with DDT and other non-pyrethroid insecticides [4]. Several studies have demonstrated a local increase in insecticide resistance in field mosquito populations following the implementation of LLINs, IRS, or both [19,20,[24][25][26] although in other locations evidence of higher resistance after the introduction of these interventions was not found [24,27]. Associations between agricultural pesticide use and insecticide resistance have also been found [21,28], and there is evidence that pesticide contamination of water bodies is a source of selection pressure for resistance acting on mosquito larvae [29].…”
Section: Introductionmentioning
confidence: 99%
“…WHO noted that 68 of the 80 malaria-endemic countries that provided data for 2010-2017 reported resistance to at least 1 of the 4 insecticide classes in one malaria vector species, while 57 countries reported resistance to 2 or more insecticide classes [8]. Existing evidence is equivocal as to whether insecticide resistance is adversely impacting malaria control, but it remains a major concern [135][136][137]. In response to the growing threat of insecticide resistance, a public-private partnership-the Innovative Vector Control Consortium-was established in 2005 to bring new insecticide chemistries to the market, which led to several ongoing market-shaping initiatives on next-generation ITNs and IRS (www.ivcc.com).…”
Section: Gmep Abandoned-what Next For Malaria?mentioning
confidence: 99%
“…The main preventive measure is sleeping under LLINs [13]. Unfortunately, resistance to pyrethroids, which is the single class of insecticides currently approved for net impregnation, is widespread in Africa [14,15]. Additionally, pyrethroid insecticides are widely used in agriculture, i.e., for rice and vegetable farming [10].…”
Section: Introductionmentioning
confidence: 99%